2016
DOI: 10.1002/2016gb005406
|View full text |Cite
|
Sign up to set email alerts
|

Rising atmospheric methane: 2007–2014 growth and isotopic shift

Abstract: From 2007 to 2013, the globally averaged mole fraction of methane in the atmosphere increased by 5.7 ± 1.2 ppb yr À1. Simultaneously, δ 13 C CH4 (a measure of the 13 C/ 12 C isotope ratio in methane) has shifted to significantly more negative values since 2007. Growth was extreme in 2014, at 12.5 ± 0.4 ppb, with a further shift to more negative values being observed at most latitudes. The isotopic evidence presented here suggests that the methane rise was dominated by significant increases in biogenic methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
485
2
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 397 publications
(549 citation statements)
references
References 69 publications
32
485
2
2
Order By: Relevance
“…2a). In an intercomparison exercise reported by Nisbet (2005), the INSTAAR measurement was +0.14 ± 0.06 ‰ higher than NIWA (not shown in Fig. 2a), which is consistent with the above value.…”
Section: Instaarsupporting
confidence: 88%
See 4 more Smart Citations
“…2a). In an intercomparison exercise reported by Nisbet (2005), the INSTAAR measurement was +0.14 ± 0.06 ‰ higher than NIWA (not shown in Fig. 2a), which is consistent with the above value.…”
Section: Instaarsupporting
confidence: 88%
“…5.11 RHUL 5.11.1 δ 13 C-CH 4 Nisbet (2005) reported that the RHUL DI-IRMS measurements agreed well with NIWA with an offset of 0.00 ± 0.02 ‰ (top in no. 11, Fig.…”
Section: δD-chmentioning
confidence: 73%
See 3 more Smart Citations